Pemikiran Pendidikan Mohammad Hatta dalam Perspektif Pendidikan Islam - Ahmad Syauqi Fuady; Samsudin (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2023)
Abstract: This article aims to analyze Mohammad Hatta's conception of educational thought from the perspective of Islamic education. Islam became an integral character of Mohammad Hatta's person, with an Islamic pattern that tends to be substantive rather than legal-formal. The writing of this article is directed to examine the extent of the influence and linkage of Mohammad Hatta's Islamic faith in the thoughts and views of education that he aspires to. This research is a library using the primary literature sources of Mohammad Hatta's writings in the Collection of Essays I and the Collection of Essays IV. The data analysis technique used is Content Analysis. The results of this study are as follows: First, faith is the main foundation in implementing Islamic education. Faith in God, as reflected in the First Precept of Pancasila, is used as a philosophical foundation for the implementation of life in aspects of government, politics, economy, socio-culture, and education. Second, knowledge for Hatta is the main instrument needed by humans in the world both to worship God and the management the universe for prosperity and well-being. Although for Hatta, science and religion have different areas of study and methods, the two cannot be separated. Third, education for Mohammad Hatta is aimed mainly at forming and creating a solid community life. Nevertheless, a stable society can be upright if individuals of faith, purity, brilliance, intelligence, intelligence and creativity sustain it. Keywords: Education, Thought, Mohammad Hatta, Islam Abstract: Artikel ini bertujuan melakukan analisis terhadap konsepsi pemikiran pendidikan Mohammad Hatta dalam perspektif pendidikan Islam. Islam menjadi karakter integral bagi pribadi Mohammad Hatta, dengan corak keberislaman yang cenderung substantif dibandingkan legal-formal. Penulisan artikel ini diarahkan untuk mengkaji sejauh mana pengaruh dan keterkaitan keberislaman Mohammad Hatta dalam pemikiran dan pandangan pendidikan yang dicita-citakan. Penelitian ini merupakan library research menggunakan sumber kepustakaan utama tulisan Mohammad Hatta dalam Kumpulan Karangan I dan Kumpulan Karangan IV. Teknik analisis data yang digunakan adalah Analisis Isi (content analysis). Hasil kajian ini adalah: Pertama, keimanan merupakan pondasi utama dalam pelaksanaan pendidikan Islam. Keimanan kepada Tuhan, sebagaimana tercermin dalam Sila Pertama Pancasila, digunakan sebagai landasan filosofis bagi pelaksanaan kehidupan baik dalam aspek pemerintahan, politik, ekonomi, sosial-budaya, dan pendidikan. Kedua, ilmu bagi Hatta adalah instrumen utama yang diperlukan oleh manusia di dunia baik untuk beribadah kepada Tuhan, maupun dalam pengelolaan alam semesta bagi kemakmuran dan kesejahteraan. Meskipun bagi Hatta ilmu dan agama memiliki wilayah kajian dan metode berbeda, keduanya tidak bisa dipisahkan. Ketiga, pendidikan bagi Mohammad Hatta ditujukan, utamanya untuk membentuk dan menciptakan kehidupan masyarakat yang kokoh. Meskipun demikian, masyarakat yang kuat dan kokoh dapat tegak jika ditopang oleh individu-individu yang beriman, bertakwa, cemerlang, pintar, cerdas dan kreatif. Keywords: Pendidikan, Pemikiran, Mohammad Hatta, Islam